Fabricação e caracterização de filmes nanoestruturados de nanotubos de carbono e polianilina para aplicação em sensores ambientais na detecção de 2-clorofenol. - Santos, Juliana de Souza (Universidade Federal de São Carlos, 2012)
Organochlorine compounds exhibit high toxicity, environmental persistence and tendency to bioaccumulate. This pollutant can spread through the air and water, affecting humans and the environment. In this context, this study aimed to develop an environmental sensor capable of detecting organochlorine compounds through nanostructured films fabricated from the layer-by-layer technique. The sensory units were composed of bilayers formed from Carbon Nanotubes (CNTs), alternated with Polyaniline (PAni). This study was divided into two main stages: the first was the fabrication and characterization of thin films and the second was the application of the film as sensor for environmental control of 2-chlorophenol. In the first stage individual films were fabricated with PAni and CNTs alternated with polyelectrolytes Poly(vinyl sulfonate) (PVS) and Poly(ethyleneimine) (PEI), respectively, and mixed film of CNTs/PAni. The films were characterized by UV-vis, FTIR and Raman spectroscopy, and by scanning electron microscopy (SEM). In the second stage sensory units were immersed in a liquid system containing 2-chlorophenol at different concentrations for characterization by means of electrochemical techniques of cyclic voltammetry and square wave voltammetry. The results of the film of CNTs/PAni showed good performance as electrochemical sensors for organochlorine compounds, since using the technique of square wave voltammetry detected the presence of 2-chlorophenol concentration from 2 ppm to the current intensity increased in about the film in individual CNTs.
-
Keywords: materiais nanoestruturados; nanotecnologia; filmes finos; nanotubos de carbono; polianilina; 2-Clorofenol; sensores; carbon Nanotubes; polyaniline; 2-Chlorophenol; sensors; OUTROS